Mengenal Konsep Dasar Evaluasi Pendidikan Pada Pembelajaran - Wijaya, Asep (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2023)
This research aims to provide basic knowledge, especially in the world of education, so that evaluation can be carried out. This research method is literature. The data collection technique used by researchers is collecting data from various library sources, including books, journals, and results. Data analysis uses data interpretation techniques and researchers provide adequate explanations in terms of theories that are relevant to the problems faced. The results of the discussion are that educational evaluation is a form of assessment of ongoing educational performance to obtain information so that it can be used to improve educational performance. There are two functions of evaluation, namely: The general function is to prepare plans and improve and measure success. Special Functions consist of administrative, psychological, and active. Meanwhile, there are specific and general goals. The principles consist of accountability, student characteristics, pedagogical, integration, and coherence. Formative, diagnostic, and summative evaluation forms. The types include monitoring evaluation, comprehensive program, impact, planning and development, and economic efficiency.